Work Stress, Fatigue, Shift Work, Workload Intensity, and Patient Safety Incidents Among Nurses - Lintang Lestari Cahya Sawitri; Bayu Anggileo Pramesona; Maya Ganda Ratna; Fitria Saftarina (Universitas Muhammadiyah Yogyakarta, 2024)
The prevalence of Patient Safety Incidents (PSIs) in Indonesia from 2015 to 2019 has increased. However, there have been limited previous studies addressing the correlation between work stress, fatigue, shift work, workload intensity, and patient safety incidents among nurses. This study aims to examine the correlation between work stress, fatigue, shift work, workload intensity, and patient safety incidents among nurses. The cross-sectional study was conducted from September to November 2023. The purposive sampling technique was used to obtain a sample of 157 respondents. Data collection used questionnaires and internal reporting of PSIs. Data analysis was performed using descriptive and Chi-Square tests. There was a significant correlation between work stress (OR=3.361, 95% CI=1.688-6.693), fatigue (OR=5.690, 95% CI=1.873-17.284), shift work (OR=1.062, 95% CI=0.560-2.015), workload intensity (OR=2.227, 95% CI=1.155-4.297), and patient safety incidents among nurses. Nurses need to be aware of their levels of stress and fatigue, and they should develop stress management and coping strategies to overcome these challenges, enabling them to work optimally. Hospital management should pay increased attention to the issues of stress and fatigue experienced by nurses, particularly those with heavy workloads and night shifts.